2006
DOI: 10.1142/s0217979206033656
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronous Random Boolean Network Model With Variable Number of Parents Based on Elementary Cellular Automata Rule 126

Abstract: A Boolean network with N nodes, each node's state at time t being determined by a certain number of parent nodes, which can vary from one node to another, is considered. This is a generalization of previous results obtained for a constant number of parent nodes, by Matache and Heidel in "Asynchronous Random Boolean Network Model Based on Elementary Cellular Automata Rule 126", Phys. Rev. E71, 026 232, 2005. The nodes, with randomly assigned neighborhoods, are updated based on various asynchronous schemes. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 23 publications
3
9
0
Order By: Relevance
“…If c n and each of its parents have the same value at time t (that is they are all either 0 or 1), then c n (t + 1) = 0, otherwise c n (t + 1) = 1. This generalizes rule 126 of cellular automata (Matache andHeidel, 2004, 2005;Wolfram, 2002). The parents of a node are chosen randomly from the remaining N − 1 nodes and do not change thereafter.…”
Section: The Random Boolean Network Modelmentioning
confidence: 72%
See 4 more Smart Citations
“…If c n and each of its parents have the same value at time t (that is they are all either 0 or 1), then c n (t + 1) = 0, otherwise c n (t + 1) = 1. This generalizes rule 126 of cellular automata (Matache andHeidel, 2004, 2005;Wolfram, 2002). The parents of a node are chosen randomly from the remaining N − 1 nodes and do not change thereafter.…”
Section: The Random Boolean Network Modelmentioning
confidence: 72%
“…In these formulae k is the number of parents of each node (considered fixed), and x t is the number of nodes to be updated at time t (randomly generated). In Matache (2006) the formula above is generalized for an arbitrary number of parents for each node. It is shown that the probability that a node is in state 1 at time t + 1 is given by…”
Section: The Random Boolean Network Modelmentioning
confidence: 99%
See 3 more Smart Citations